Perspective by incongruity: Law and rhetoric in Masterpiece Cakeshop v. Colorado Civil Rights Commission. Issue 1 (2nd January 2020) - Eisenstadt, Michael
ABSTRACT: The Supreme Court's ruling in Masterpiece Cakeshop v. Colorado Civil Rights Commission was decided on the narrow ground that the Colorado Civil Rights Commission violated the First Amendment's Free Exercise Clause because of hostility toward the owner of Masterpiece Cakeshop. This decision failed to answer a cardinal question of constitutional law, whether or not the First Amendment's Free Speech Clause could undermine nondiscrimination law. In Justice Anthony Kennedy's majority opinion, he seized on one particular comment made by a Commissioner about religious freedom that justified ruling against the Commission for its use of discriminatory rhetoric. According to Justice Kennedy, the Commission violated the Free Exercise Clause by describing religious expression as despicable and as merely rhetorical . In this report, I argue that Justice Kennedy's opinion demands heightened attention for two reasons. First, to describe religious freedom as a justification for prejudice as merely rhetorical is a gross underestimation of the power of rhetoric and provides moral encouragement to anti-LGBTQ+ activists using the legal system to advance a heteronormative agenda. Second, Justice Kennedy's claim that rhetoric is insubstantial and insincere calls into question the role of the Court, the meaning of the law, and the relationship between the law and rhetoric.